Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1056/nejm199508313330901
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and Misoprostol to Terminate Early Pregnancy

Abstract: The combination of methotrexate and misoprostol represents a safe and effective alternative to invasive methods for the termination of early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(39 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Once Hausknecht [2] demonstrated that women could leave the office as soon as misoprostol was administered and handle the expulsion on their own, subsequent studies explored dispensing misoprostol to women for home use. These studies demonstrated that women were able to follow instructions and take the misoprostol as directed and led to the elimination of a clinic visit.…”
mentioning
confidence: 99%
“…Once Hausknecht [2] demonstrated that women could leave the office as soon as misoprostol was administered and handle the expulsion on their own, subsequent studies explored dispensing misoprostol to women for home use. These studies demonstrated that women were able to follow instructions and take the misoprostol as directed and led to the elimination of a clinic visit.…”
mentioning
confidence: 99%
“…In our study, the rate of complete abortions with methotrexate and intravaginal misoprostol for the termi nation of pregnancies < 8 weeks gestation was found to be only 71.8%, whereas Creinin [6,7], Hausknecht [9] and Schaff [10] reported 90, 96 and 97% success rates, respec tively. Several reasons may account for this significant difference.…”
Section: Discussionmentioning
confidence: 55%
“…Methotrexate is teratogenic and may induce abortion (275,296,312,329). Methotrexate is toxic to embryonic or trophoblastic tissues and has been used to terminate ectopic pregnancies (330).…”
Section: Adverse Effects Of Methotrexatementioning
confidence: 99%